Discrimination of fibrotic staging of chronic hepatitis C using multiple fibrotic markers. Issue 11 (18th September 2013) - Ikeda, Kenji; Izumi, Namiki; Tanaka, Eiji; Yotsuyanagi, Hiroshi; Takahashi, Yoshihisa; Fukushima, Junichi; Kondo, Fukuo; Fukusato, Toshio; Koike, Kazuhiko; Hayashi, Norio; Tsubouchi, Hirohito; Kumada, Hiromitsu
<x xml:space="preserve">Abstract</x> Aim In order to evaluate and judge a fibrotic stage of patients with chronic hepatitis C, multivariate regression analysis was performed using multiple fibrotic markers. Methods A total of 581 patients from eight hepatology units and institutes were diagnosed by needle biopsy as having chronic liver disease caused by hepatitis C virus. Twenty‐three variables and their natural logarithmic transformation were employed in the multivariate analysis. Results Multivariate regression analysis finally obtained the following function: z = 2.89 × ln (type IV collagen 7S) (ng/mL) − 0.011 × (platelet count) (×103/mm3) + 0.79 × ln (total bilirubin) (mg/dL) + 0.39 × ln (hyaluronic acid) (μg/L) − 1.87. Median values of the fibrotic score of F1 (n = 172), F2 (n = 80), F3 (n = 37) and F4 (n = 16) were calculated as 1.00, 1.45, 2.82 and 3.83, respectively. Multiple regression coefficient and coefficient of determination were 0.56 and 0.320, respectively. Validation with patient data from other institutions demonstrated good reproducibility of the fibrotic score for hepatitis C (FSC), showing 1.10 in F1 (n = 156), 2.35 in F2 (n = 73), 3.16 in F3 (n = 36) and 3.58 in F4 (n = 11). Conclusion A concise multiple regression function using four laboratory parameters successfully predicted pathological fibrotic stage of patients with hepatitis C virus infection.